The Desiring-Image: Gilles Deleuze and Contemporary Queer Cinema/Ethereal Queer: Television, Historicity, Desire - Betancourt, Manuel (Film Quarterly, 2013)
Betancourt reviews The Desiring-Image: Gilles Deleuze and Contemporary Queer Cinema by Nick Davis and Ethereal Queer Television, Historicity, Desire by Amy Villarejo.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé